Potential Benefits and Shortcomings of Marine Protected Areas for Small Seabirds Revealed Using Miniature Tags - Maxwell, Sara M.; Conners, Melinda G.; Sisson, Nicholas B.; Dawson, Tiffany M. (Frontiers in Marine Science, 2016)
Marine protected areas are considered important tools for protecting marine biodiversity, and animal tracking is a key way to determine if boundaries are effectively placed for protection of key marine species, including seabirds. We tracked chick-rearing brown noddies (Anous stolidus) from the Dry Tortugas National Park in Florida USA in 2016 using 1.8 g Nanofix GPS tags (n = 10), making this the first time this species has ever been tracked. We determined movement parameters, such as flight speed, distance traveled and home range, and how birds used a complex of marine protected areas including the Dry Tortugas National Park which is largely no-take (i.e., no fishing or extraction permitted), and the Florida Keys National Marine Sanctuary, of which two Ecological Reserves totaling 517.9 km2 are no-take. Birds remained largely within marine protected areas, with 91.3% of birds’ locations and 58.8% of the birds’ total home range occurring within the MPAs, and 79.2% of birds’ locations and 18.2% of the birds’ total home range within no-take areas. However areas of probable foraging, indicated by locations where birds had high-residence time, were found within one of the MPAs only 64.7% of the time, and only 6.7% of those locations were in no-take areas. Birds traveled a mean straight line distance from the colony of 37.5 km, primarily using the region to the southwest of the colony where the shelf break and Loop Current occur. High-residence-time locations were found in areas of significantly higher sea surface temperature and closer to the shelf break than low residency locations. A sea surface temperature front occurs near the shelf edge, likely indicative of where Sargassum seaweed is entrained, providing habitat for forage species. Much of this region, however, falls outside the boundaries of the marine protected areas, and brown noddies and other species breeding in the Dry Tortugas may interact with fisheries via resource competition or discard foraging. The complex of marine protected areas in the region encompasses a large portion of the overall habitat for this small seabird species, however a large portion of the key foraging habitat fell outside the boundaries of the